2010
DOI: 10.3389/fpsyg.2010.00177
|View full text |Cite
|
Sign up to set email alerts
|

ERP Evidence for Ultra-Fast Semantic Processing in the Picture–Word Interference Paradigm

Abstract: We used the event-related potential (ERP) approach combined with a subtraction technique to explore the timecourse of activation of semantic and phonological representations in the picture–word interference paradigm. Subjects were exposed to to-be-named pictures superimposed on to-be-ignored semantically related, phonologically related, or unrelated words, and distinct ERP waveforms were generated time-locked to these different classes of stimuli. Difference ERP waveforms were generated in the semantic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
121
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 45 publications
(50 reference statements)
23
121
2
3
Order By: Relevance
“…Our observation of a smaller N400 amplitude for semantically related than for unrelated distractor words replicates the findings of Blackford et al (2012) and Dell'Acqua et al (2010), although the smaller negativity for semantic than for unrelated distractors in the N400 time window was not identified as an N400 effect by Dell'Acqua et al Our data show that the attenuation of the N400 by semantic relatedness is also obtained across languages.…”
Section: Comparisons With Earlier Findingssupporting
confidence: 76%
“…Our observation of a smaller N400 amplitude for semantically related than for unrelated distractor words replicates the findings of Blackford et al (2012) and Dell'Acqua et al (2010), although the smaller negativity for semantic than for unrelated distractors in the N400 time window was not identified as an N400 effect by Dell'Acqua et al Our data show that the attenuation of the N400 by semantic relatedness is also obtained across languages.…”
Section: Comparisons With Earlier Findingssupporting
confidence: 76%
“…This has lead to the assumption of a bimodal distribution of scalp activity for the semantic effects. The primary component was characterized by a fast onset with a sharp increase during the first 50 ms past stimulus onset and a decrease after 200 ms (Dell'Acqua et al, 2010). Although this working group usually focuses on a variety of components, their results correspond with those from the previously mentioned studies regarding the timing of processing.…”
Section: Realistic Time Frames For Turn-end-detectionsupporting
confidence: 74%
“…For these visually presented Chinese characters, the earliest neural signature appeared 80 ms after stimulus onset (Skrandies et al, 2004). Dell'Acqua et al (2010) achieved similar results when they studied the activation time of semantic and phonological representation. The obtained ERP results showed a primary component and a later, distinct component.…”
Section: Realistic Time Frames For Turn-end-detectionmentioning
confidence: 50%
“…In addition to behavioural latencies, results from EEG (electroencephalography) were measured. Previous studies which had used EEG in conjunction with PWI studies had shown event-related potentials (ERPs) evoked by the two types of relatedness which appeared in roughly the same time window relative to picture onset (e.g., Dell'Acqua et al, 2010). By contrast, we found a serial pattern, with semantic effects appearing in a time window of 250-450 ms and phonological effects in a time window of 450-600 ms.…”
contrasting
confidence: 45%